Adverse reaction to metal debris in a painful hemiarthroplasty of the hip - Palmer, Jonathan Simon (J Surg Case Rep, 2016)
Adverse reaction to metal debris (ARMD) in total hip arthroplasty surgery is a well-known problem. We present the case of a unipolar hemiarthroplasty requiring revision within 18 months of insertion secondary to an adverse reaction to metal debris. This case demonstrates a rare cause for failure of a hemiarthroplasty following a fragility fracture. We feel that ARMD should be considered in all cases where pain and dysfunction in the presence of any hip prosthesis cannot be explained by routine investigations.